Methods and theory of teaching physical education in primary school (Eurasian Journal of Learning and Academic Teaching, 2022)
Currently, the development of new theories and practices of physical education, including the upbringing of children and adolescents, their socio-pedagogical support and protection is a process that is considered an integral part of individual-oriented integrated physical education.